An Autoethnographic Journey Into Uncovering Additional Types Of Entrepreneurial Intuition - Bayat, Abdullah; Haarhoff, Rene (Research Collaboration Community (RCC), 2024)
Although writing on entrepreneurial intuition has grown, researchers maintain that there is still much to explore. Current research has looked at the types of entrepreneurial intuition as well as the nature of cognitive intuitive thinking. The research problem explored is that entrepreneurial intuition should not be limited to the four types proposed. To address the entrepreneur’s cognitive intuitive strategies, it has been suggested that research should focus on what happens inside the mind of the entrepreneur. To pursue this further, we adopted a collaborative autoethnographic approach which consists of the self-study of an entrepreneur and the addition of a researcher to act as a reflective sounding board. Six story boxes tell intuitive stories of entrepreneurship. This research study finds that the cognitive, intuitive thinking strategies pursued by the entrepreneur extend beyond the four basic types suggested and two additional intuitive practices, namely sensorial intuition and intuitive praxis are proposed for this multifaceted concept. Used interchangeably, these intuitive practices are situational allowing the entrepreneur to act intuitively within various contexts. The recommendations are that these findings can be further investigated through quantitative studies.